2023
DOI: 10.3390/ma17010148
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Deep Neural Networks for Estimating Vickers Hardness from Nanoindentation Hardness

Junbo Niu,
Bin Miao,
Jiaxu Guo
et al.

Abstract: This research presents a comprehensive analysis of deep neural network models (DNNs) for the precise prediction of Vickers hardness (HV) in nitrided and carburized M50NiL steel samples, with hardness values spanning from 400 to 1000 HV. By conducting rigorous experimentation and obtaining corresponding nanoindentation data, we evaluated the performance of four distinct neural network architectures: Multilayer Perceptron (MLP), Convolutional Neural Network (CNN), Long Short-Term Memory network (LSTM), and Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…This opened up new possibilities in the field of indentation techniques. With the continuous advancement of technology, there is a growing demand for understanding the mechanical properties of materials, such as hardness [3][4][5][6][7], Young's modulus [8][9][10][11][12], residual stress [13][14][15][16][17], and plasticity [18][19][20][21][22]. These studies have demonstrated that the mechanical properties of materials can be extracted by comparing the load-displacement curves obtained from finite element simulations with those obtained from experimental measurements when the data are in good agreement.…”
Section: Introductionmentioning
confidence: 99%
“…This opened up new possibilities in the field of indentation techniques. With the continuous advancement of technology, there is a growing demand for understanding the mechanical properties of materials, such as hardness [3][4][5][6][7], Young's modulus [8][9][10][11][12], residual stress [13][14][15][16][17], and plasticity [18][19][20][21][22]. These studies have demonstrated that the mechanical properties of materials can be extracted by comparing the load-displacement curves obtained from finite element simulations with those obtained from experimental measurements when the data are in good agreement.…”
Section: Introductionmentioning
confidence: 99%